Maternal Obesity during Pregnancy is Associated with Lower Cortical Thickness in the Neonate Brain - Na, X.; Phelan, N.E.; Tadros, M.R.; Wu, Z.; Andres, A.; Badger, T.M.; Glasier, C.M.; Ramakrishnaiah, R.R.; Rowell, A.C.; Wang, L.; Li, G.; Williams, D.K.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Recent studies have suggested that maternal obesity during pregnancy is associated with differences in neurodevelopmental outcomes in children. In this study, we aimed to investigate the relationships between maternal obesity during pregnancy and neonatal brain cortical development.MATERIALS AND METHODS: Forty-four healthy women (28 normal-weight, 16 obese) were prospectively recruited at <10 weeks’ gestation, and their healthy full-term neonates (23 boys, 21 girls) underwent brain MR imaging. All pregnant women had their body composition (fat mass percentage) measured at ∼12 weeks of pregnancy. All neonates were scanned at ∼2 weeks of age during natural sleep without sedation, and their 3D T1-weighted images were postprocessed by the new iBEAT2.0 software. Brain MR imaging segmentation and cortical surface reconstruction and parcellation were completed using age-appropriate templates. Mean cortical thickness for 34 regions in each brain hemisphere defined by the UNC Neonatal Cortical Surface Atlas was measured, compared between groups, and correlated with maternal body fat mass percentage, controlled for neonate sex and race, postmenstrual age at MR imaging, maternal age at pregnancy, and the maternal intelligence quotient and education.RESULTS: Neonates born to obese mothers showed significantly lower (P ≤ .05, false discovery rate–corrected) cortical thickness in the left pars opercularis gyrus, left pars triangularis gyrus, and left rostral middle frontal gyrus. Mean cortical thickness in these frontal lobe regions negatively correlated (R = –0.34, P = .04; R = –0.50, P = .001; and R = –0.42, P = .01; respectively) with the maternal body fat mass percentage measured at early pregnancy.CONCLUSIONS: Maternal obesity during pregnancy is associated with lower neonate brain cortical thickness in several frontal lobe regions important for language and executive functions.BMIbody mass indexFDRfalse discovery rateIQintelligence quotient